LA REVOLUCIÓN QUE NO REDIMIÓ AL INDIO ECUATORIANO - Albornoz , César (2024)
Liberal instauration in Ecuadorian society involves a long process that began with the struggle for independence and continued up to the triumph of the Liberal Revolution in 1895. In this bloody and epic deed new conquests were achieved, but also many popular claims were frustrated: the land problem, and the lndian in between, which both are still pending today. This paper discusses how several factors in the decisive years of the liberal revolution prevented to go further in the solution of these popular and essential claims, with its subsequent impact on the future of the country.